2020
DOI: 10.1215/0961754x-8188868
|View full text |Cite
|
Sign up to set email alerts
|

Votive Exopraxis

Abstract: Twice a year, the Greek Orthodox Monastery of St. George on the island of Büyükada, off the coast of Istanbul, attracts tens of thousands of Muslim pilgrims who come to make heterogenous and inventive votive offerings. Since these visitors are not Christians, their behavior is a form of exopraxis, which is the subject of the issue of Common Knowledge in which this contribution appears. Due to its scope and dynamism, this shared pilgrimage is perhaps the most important in the contemporary religious landscape of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…(Plate 7). Fliche and Pénicaud (2020) observed that between 2006 and 2014, it also occurs with amulets whose number increased from 12 to 27, some specifically relating to military service, exams, disability, sorrow, success, freedom, etc.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(Plate 7). Fliche and Pénicaud (2020) observed that between 2006 and 2014, it also occurs with amulets whose number increased from 12 to 27, some specifically relating to military service, exams, disability, sorrow, success, freedom, etc.…”
Section: Resultsmentioning
confidence: 99%
“…However, they never manage to fully contain/prevent heteropraxis, i.e. practices considered deviant and heterodox (Fliche and P enicaud, 2020). This is obvious in the case of pilgrimages: religious authorities (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations